2022
DOI: 10.3390/ijms232012599
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Citrullinated Peptide Antibodies Control Oral Porphyromonas and Aggregatibacter species in Patients with Rheumatoid Arthritis

Abstract: Oral microbiome changes take place at the initiation of rheumatoid arthritis (RA); however, questions remain regarding the oral microbiome at pre-RA stages in individuals with clinically suspect arthralgia (CSA). Two cross-sectional cohorts were selected including 84 Tatarstan women (15 early-RA as compared to individuals with CSA ranging from CSA = 0 [n = 22], CSA = 1 [n = 19], CSA = 2 [n = 11], and CSA ≥ 3 [n = 17]) and 42 women with established RA (median: 5 years from diagnosis [IQ: 2–11]). Amplicon sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In other words, "RA" may arise as a consequence of a number of different pathways that differ according to the RA phenotypes and infections [7]. Fourth, the genetic and immunological status at RA onset may be important, such an assertion has been reinforced by our report showing that the oral microbiome is tightly controlled in RA patients with elevated anti-cyclic citrullinated peptide antibodies (CCPs) [8].…”
Section: Introductionmentioning
confidence: 94%
“…In other words, "RA" may arise as a consequence of a number of different pathways that differ according to the RA phenotypes and infections [7]. Fourth, the genetic and immunological status at RA onset may be important, such an assertion has been reinforced by our report showing that the oral microbiome is tightly controlled in RA patients with elevated anti-cyclic citrullinated peptide antibodies (CCPs) [8].…”
Section: Introductionmentioning
confidence: 94%
“…In a previous study, 26 FDR women having developed RA were studied at different time points showing a relationship between joint symptoms and then susceptibility to upper respiratory tract infection events in 3 years preceding the RA onset ( 4 ). In this cohort, herpes simplex virus (HSV) reactivation and oral microbiome changes also characterize the familial RA onset ( 5 , 6 ). To proceed further with the analysis of this cohort, 144 RA patients with a familial RA history were included when a rheumatological evaluation and information regarding socio-demographic and individual behavior factors were recorded at least 2 years before the RA onset.…”
Section: Introductionmentioning
confidence: 99%
“…Oral microbiome changes take place at the initiation of RA. Arleevskaya M et al [ 13 ] reported that anti-citrullinated peptide antibodies control periodontal bacteria such as oral porpyromonas and aggregatibacter species in patients with RA. In the RA-established cohort, porpyromonas sp.…”
mentioning
confidence: 99%